2014
DOI: 10.1039/c4cc05735j
|View full text |Cite
|
Sign up to set email alerts
|

Aurophilically cross-linked “dynamic” hydrogels mimicking healthy synovial fluid properties

Abstract: We report a new supramolecular dynamic hydrogel, based on a new concept of reversible aurophilic cross-linkers, mimicking the rheological behaviour of healthy synovial fluid under physiological conditions with good cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…The selection of (PEGSH) 4 with an existing cross-linking point to strengthen the final hydrogel was justified, as linear PEG(SH) 2 only led to chain extension after aerial oxidation, as previously reported. 32 Unlike Au20, free-standing PEGSS hydrogel was observed at all pHs. Clearly, the presence of Au−S species is responsible for the dynamic character observed for Au20 at alkaline pH.…”
Section: ■ Experimental Sectionmentioning
confidence: 94%
“…The selection of (PEGSH) 4 with an existing cross-linking point to strengthen the final hydrogel was justified, as linear PEG(SH) 2 only led to chain extension after aerial oxidation, as previously reported. 32 Unlike Au20, free-standing PEGSS hydrogel was observed at all pHs. Clearly, the presence of Au−S species is responsible for the dynamic character observed for Au20 at alkaline pH.…”
Section: ■ Experimental Sectionmentioning
confidence: 94%
“…11 Among the resulting supramolecular structures obtained with low molecular weight gold(I) complexes, recent reports on hydrogelators should be highlighted. [12][13][14] The formation of these gels has been driven through non-covalent interactions, which are commonly van der Waals forces, hydrogen bonding, electrostatic attractions and  stacking interactions, together with aurophilic interactions. 12 Our recent results on the formation of hydrogels from small organometallic complexes containing Au(I)-alkynyl moieties, [15][16][17] prompted us to go one step further in the design and synthesis of novel supramolecular nanostructures constituted by selfassembly of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Similar differences can also be found among novel systems proposed as candidates for viscosupplementation. 40,[42][43][44][45] Tests performed on blends with different gel fractions have shown that an acceptable structural recovery after continuous shear application (more than 80-90 %) is attained when the gel fraction is lower than 50 %. Thus, the 6/4 CMCAp/CMCAg blend has been provisionally selected for the final investigation addressed to individuate the most suitable total polymer concentration, apt to compensate the loss in mechanical properties occurring during processing and sterilization.…”
Section: F I G 4 -Viscoelastic Responses Of 25 % Cmcap and 25 % Cmentioning
confidence: 99%